Load Frequency control of two area system with PI & Fuzzy (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
In the recent time the fuzzy logic controller to control a nonlinear process has received wide attention. A single generator unit feed a power line to various users whose power demand can vary over time to time, is called a nonlinear process. If there is a change in load demand then there is a change in the frequency of the generator.This thesis presents a procedure to design controller based on fuzzy logic and PI to control the load frequency variations in on efficient manner. Two types of plant are studied – single area thermal plant, two area thermal- thermal plant. In this thesis work Adaptive fuzzy logic gain scheduling controllers are designed which change the controllers parameters according to variations. The results show the superiority of the fuzzy logic and gain scheduling over the PI controller. In the simulations a linear model of power system is used.